Les attributs linguistiques et la détermination du revenu des hommes au Québec en 1971 : les groupes d’âge et d’éducation - Vaillancourt, François (L'Actualité économique)

(untitled) (HEC Montréal, 1979)
This paper examines the role that language skills play in the determination of the labour earnings of Quebec males in 1971 both for all males and for age and education specific subgroups. The first part of the paper presents the conceptual framework and the gross earnings differences between anglophones and francophones in Quebec. The second part describes the data and the variables used and the third and fourth parts contain the regression results and a discussion of the economic meaning of these results. In a nutshell these results indicate that knowing English is a more highly rewarded skill than knowing French in Quebec in 1970 and that the returns vary with the age but not with the education of Quebec males.